Cluster governance of School-university clusters (New Collegium, 2020)
University-School clusters: Best practices and the prospects for their adaptation to Ukrainian context : the XVIII International Scientific and Practical Conference (14-th Febuary 2020, Kharkiv Univ. of Humanities “People’s Ukrainian Acad”. The proceedings of the XVIII International Scientific and Practical Conference “University-School clusters: include a variety of articles on the issues of the formation of a cluster-based educational model and its role in the development of the educational space. Covered are the essence of university-school clusters, the conceptual framework for their evolvement, development, and functioning in todays context with special attention paid to the models of the university management under the cluster-based educational system as well as to the problems and prospects of interaction between the key stakeholders in cluster systems.